X⁵+ x +2x³ + 6+ 2x² = x⁵ + 2x³ +2x² + x + 6
Step-by-step explanation:
-7(-4p+1) + 2p
-7 x -4 = 28p
-7 x 1 = -7
28p + 2p = 30p
so
30p-7
The answer is x=
-3
Hope I helped!
Ok so first we need to distribute so:
<span>=<span><span><span><span><span>(4)</span><span>(b)</span></span>+<span><span>(4)</span><span>(2)</span></span></span>+</span>−<span>3b
</span></span></span>=<span>4b+8+−3b
</span>So now that we've distrubuted that we are now going to Combine Like Terms:
<span>=<span><span><span>4b</span>+8</span>+<span>−<span>3b
</span></span></span></span><span>=<span><span>(<span><span>4b</span>+<span>−<span>3b</span></span></span>)</span>+<span>(8)
Finally your answer is:
</span></span></span><span>=<span>b+<span>8
I hope this helps you!</span></span></span>